Genome‐wide DNA methylation analysis of colorectal adenomas with and without recurrence reveals an association between cytosine‐phosphate‐guanine methylation and histological subtypes - David Fiedler (2672563) (2019)
Aberrant methylation of DNA is supposed to be a major and early driver of colonic adenoma development, which may result in colorectal cancer (CRC). Although gene methylation assays are used already for CRC screening, differential epigenetic alterations of recurring and nonrecurring colorectal adenomas have yet not been systematically investigated. Here, we collected a sample set of formalin‐fixed paraffin‐embedded colorectal low‐grade adenomas (n = 72) consisting of primary adenomas without and with recurrence (n = 59), recurrent adenomas (n = 10), and normal mucosa specimens (n = 3). We aimed to unveil differentially methylated CpG positions (DMPs) across the methylome comparing not only primary adenomas without recurrence vs primary adenomas with recurrence but also primary adenomas vs recurrent adenomas using the Illumina Human Methylation 450K BeadChip array. Unsupervised hierarchical clustering exhibited a significant association of methylation patterns with histological adenoma subtypes. No significant DMPs were identified comparing primary adenomas with and without recurrence. Despite that, a total of 5094 DMPs (false discovery rate <0.05; fold change >10%) were identified in the comparisons of recurrent adenomas vs primary adenomas with recurrence (674; 98% hypermethylated), recurrent adenomas vs primary adenomas with and without recurrence (241; 99% hypermethylated) and colorectal adenomas vs normal mucosa (4179; 46% hypermethylated). DMPs in cytosine‐phosphate‐guanine (CpG) islands were frequently hypermethylated, whereas open sea‐ and shelf‐regions exhibited hypomethylation. Gene ontology analysis revealed enrichment of genes associated with the immune system, inflammatory processes, and cancer pathways. In conclusion, our methylation data could assist in establishing a more robust and reproducible histological adenoma classification, which is a prerequisite for improving surveillance guidelines. Other Information Published in: Genes, Chromosomes and Cancer License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/gcc.22787